Methodical Recommendation for the Use of Information Technology in Primary Classes - Bayramberdiyev Nurnazar Bagibek ogli (Universitas Muhammadiyah Sidoarjo, 2022)
This article provides information on the importance of using information technology in primary classes. It is known that primary education is the foundation of the educational system, the quality of teaching students will depend on it, and this will be a great responsibility on the part of the primary school teacher. For a long time in the educational system, the primary school was considered a